Síntese, caracterização e avaliação in silico de derivados de chalconas heterocíclicas como potenciais broncodilatadores - Duarte, Gabrielly Diniz (2020)
Chalcones are molecules of high biological value due to it’s variety in biological activities. In this context, derivatives of synthetic chalcones are promising molecules in drug development of interest for both the academy and industry. Seeking to contribute to the diversity of synthetic molecules and the study of new bronchodilators, this work aimed at the synthesis and characterization of a thiophenic chalcone (E)-1-(benzo [d][1,3]dioxol-5-yl)-3-(thiophen-2-yl)prop-2-en-1-one (GA-01) and three unpublished derivatives, these being: 3-(benzo[d][1,3]dioxol-5-yl)-5- (thiophen-2-yl)-4,5-dihydro-1H-pyrazol-1-carbothioamide (GA-04), 3-(benzo[d][1,3] dioxol-5-yl)-1-phenyl-5-(thiophen-2-yl)-4,5-dihydro-1H-pyrazole (GA-05) and 1-(3- (benzo[d][1,3]dioxol-5-yl)-5-(thiophen-2-yl)-4,5-dihydro-1H-pyrazol-1-yl)ethan-1-one (GA-06). Reaction yields varied between 93.8% and 31.83% and the compounds were obtained by precipitation, avoiding costs with exhaustive steps of purification. All molecules were subjected to in silico tests for their bronchodilator activity and for it’s pharmacokinetic properties. In the tests mentioned above, the substances GA-01, GA-05 and GA-06 showed potential bronchodilator activity.